High-dose probiotic supplementation containing Lactobacillus casei for 7 days does not enhance salivary antimicrobial protein responses to exertional heat stress compared with placebo - Gill, S. K.; Teixeira, A. M.; Cox, M.; Rosado, F.; Soares Costa, R. J. (International Journal of Sport Nutrition and Exercise Metabolism, 2016)
The study aimed to determine whether high-dose probiotic supplementation containing Lactobacillus casei (L. casei) for 7 consecutive days enhances salivary antimicrobial protein (S-AMP) responses to exertional-heat stress (EHS). Eight endurance-trained male volunteers (age 26 ± 6 years, nude body mass 70.2 ± 8.8 kg, height 1.75 ± 0.05 m, VO2max 59 ± 5 ml·kg-1·min-1 [M ± SD]) completed a blinded randomized and counterbalanced crossover design. Oral supplementation of the probiotic beverage (PRO; L. casei × 1011 colony-forming units·day-1) or placebo (PLA) was consumed for 7 consecutive days before 2 hr running exercise at 60% VO2max in hot ambient conditions (34.0 °C and 32% RH). Body mass and unstimulated saliva and venous blood samples were collected at baseline (7 days before EHS), pre-EHS, post-EHS (1 hr, 2 hr, and 4 hr), and at 24 hr. Saliva samples were analyzed for salivary (S) IgA, a-amylase, lysozyme, and cortisol. Plasma samples were analyzed for plasma osmolality. Body mass and plasma osmolality did not differ between trials. Saliva flow rate remained relatively constant throughout the experimental design in PRO (overall M ± SD = 601 ± 284 µl/min) and PLA (557 ± 296 µl/min). PRO did not induce significant changes in resting S-AMP responses compared with PLA (p > .05). Increases in S-IgA, S-a-amylase, and S-cortisol responses, but no S-lysozyme responses, were observed after EHS (p < .05). No main effects of trial or Time × Trial interaction were observed for S-AMP and S-cortisol responses. Supplementation of a probiotic beverage containing L. casei for 7 days before EHS does not provide any further oral-respiratory mucosal immune protection, with respect to S-AMP, over PLA.